Hubungan Pengetahuan dan Sikap Ibu dengan Penanggulangan ISPA pada Balita - Susan Susyanti; Egi Ariandoni; Tanti Suryawantie (Jurnal Medika Cendikia, 2017)
Acute Respiratory Infection (ISPA) is a disease that often occurs in children. ISPA incidence in infants is estimated to reach 0.29 episodes every child in every year in developing countries and 0.05 episodes every child in every year in developed countries. It shows that there are 156 million new episode in the world every year, of which 151 million episodes (96.7%) occur in developing countries. The purpose of this study was to determine the relationship between knowledge and mother's demeanor to ISPA response in toddler. The research design was descriptive correlational cross-sectional approach. The population in this study are all mothers who have children (1-5 years) in the village of Mekarwangi, the study sample was 54 mothers who have children have ISPA experienced or never have ISPA experienced in the village Mekarwangi with sampling technique using proportional random sampling. From the results, the majority of respondents knowledgeable enough (50,0%), some less knowledgeable respondents (38.9%) and very few of the respondents good knowledge (11.1%). Most of the respondents have a supportive attitude (64.8%) and a small portion of the respondents had an attitude does not support (35.2%). Most of rersponden have ISPA positive response (68.5%) and a small percentage of respondents had ISPA negative response (31.5%). Results obtained chi-square test of the relationship between mothers' knowledge with ISPA response in toddler (p-value 0.000 <0.05) and there is a relationship between the attitude of mothers with ISPA response in toddler (p-value 0.014 <0.05). Based on these results it can be concluded that there is a relationship between knowledge and mothers' demeanor with ISPA response in toddler so it is recommended for health workers to further improve back health education in the field of child health and combating infectious diseases, especially ISPA so that the next time the incidence of ISPA not high again.